Socio-Economic Impact of Cervical Spinal Cord Injury Operated in Patients with Lower Income Group. Issue 1 (April 2016) - Goel, Shakti Amar; Modi, Hitesh N.; Dave, Bharat R.; Patel, Pankaj R.
Introduction: None of study reviewed on socio-economic impact after cervical spine surgery in patients with cervical spine injury or myelopathy. Aim was to study clinico-radiological results and socio-economic impact even after radiologically successful surgery. Methods: After board approval, 104 participants (56 traumatic, 48 myelopathy) were included. All patients were operated at a single institute between 2007 and 2014 with anterior cervical approach. Patients who were expired after surgery and other pathology were excluded, as aim was to study socio-economic aspect. Nurick scale was used to assess the degree of loss of function in individuals and roentograms for fixation assessment. Results: The average age of study group was 46.65 years with 58% comprising of males( n  = 63). About 46.7% of the study group were laborers or farmers, majority of whom lost their jobs (47%) post injury. None of the patient had medical or life insurance. Average expenditure per family of < 40USD per month. About 19% of the monthly expenditure was spent on their illness; still majority (56%) had aspirations to get the government support in form of financial help or rehabilitation. The Nurick scale did not show any significant change in pre and post operative periods (3.06 v/s 2.83, p > 0.05). Despite good radiological results; the socioeconomic burdens in study group had little impact. Conclusion: Study shadowed socioeconomic impact after cervical spine injury and are first of its kind in lower income group. Such studies may further throw light in future management of cervical spine injuries in developing versus developed world.